Language Acquisition Process in Children Aged 4 Years: Syntactic Development Stage - Annisa Faradilla; Sholihatul Hamidah Daulay (ELITE JOURNAL, 2023)
This research aims to discuss children’s first language acquisition process at age 4 years old. The purpose of this research is to explain how the children learn and acquire the language in real life. This research is conducted with descriptive qualitative research method. The data is taken from a child named Shakir Mumtaz who lives in Sunggal, Medan. The data obtained by the result of observation and interviews. The result of this research finds out that Shakir was a 4 years old’s child who was able to pronounce the elements of complicated structure such as simple sentence or it called by later multiword stage of language development. Finally, in children’s first language acquisition process, the role of their parents was so important. The child’s language development can be built by the good interaction between parents and children. Thus, the researcher suggests to the parents to speak with good pronunciation to the early childhood. Keywords: first language, language acquisition, acquisition of syntax.